Experimental study and theoretical analysis for the synchronous-concentric inclined pile composed of steel pipe pile and cemented soil - Jun-Neng, Ye; Zhong-Jin, Wang; Kai-Chen, Zhu; Shi-Yong, Shi; Hong-Hui, Mao; Qian-Hao, Wang (Frontiers in Earth Science, 2025)
As a new type of composite pile, the synchronously and concentrically constructed steel pipe–cemented soil composite pile has been increasingly adopted as an inclined support system in foundation pit engineering. However, theoretical research on the mechanical behavior and calculation methods of this composite pile has lagged behind its practical engineering applications. In this study, a series of laboratory tests were conducted to investigate the interaction between the steel pipe and the surrounding cemented soil. A novel calculation method is proposed for the bearing capacity and deformation behavior of the new composite inclined pile. In this new model, the steel pipe and the inner cemented soil are assumed to have no relative displacement and are treated as a single pile body using an equivalent modulus approach. The surrounding cemented soil primarily undergoes shear deformation, and its interaction with the natural soil is also modeled as ideal elastoplastic. The end resistance–displacement behavior of the cemented soil is described using a hyperbolic relationship. The influence of key parameters on the pile performance was also analyzed. Practical methods for determining the main parameters were provided. The results show that the proposed calculation method agrees well with the engineering measurements, demonstrating its applicability for evaluating the bearing characteristics of this new composite pile type and offering valuable guidance for practical engineering design and implementation.